FAKTOR EKONOMI DAN KELEMBAGAAN DALAM KEBERLANJUTAN CREDIT UNION DI INDONESIA - , Titus Odong Kusumajati, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study focuses on exploring the role of institutional and economic factors that affect the achievement of self-reliance and sustainability of the Credit Union in Indonesia. This study employs a mixed analysis methods, the method of quantitative analysis and qualitative analysis, and implements the strategy of case study with embedded design. The results show that Credit Unions in Indonesia are a financial institution that can play a role in a sustainable manner because they are built in accordance with the needs of the communities it serves, supported by a conducive institutional environment, and financially self-reliant. The sustainability of Credit Union in Indonesia is supported by the results of research that state that the Credit Union's performance is supported by social and cultural factors, especially the local custom which serves as an important consideration in the design of saving and loan products, and services mechanism and rules of Credit Union governance. Credit Union in Indonesia can also be categorized as a sustainable financial institutions that is sound and profitable, being able to achieve effective financial structure, able to manage liquidity well, and able to operate profitably.